The conference of the family group (KGR) as a method of theworking with the families in danger of social exclusion (results of the work District Centre of the Family Help in Bytów) - Lesner, Wiesław; Wirkus, Katarzyna (Karkonoska Państwowa Szkoła Wyższa, 2011)
Conference of the family group (KGR) is a method of the work with the family leading families in functioning to positive changes, giving the possibility of constructive and effective solving her problems. The specificity of this method causes employing the wide circle of members of a family, as well as other persons important for the child: of acquaintances, of neighbors, of friends; on the established forum discussion is being entered into with the possibility of using the participation of professionals, granting technical consultation; plans concerning solving difficult situations of the child and the family are being formulated. The KGR method is applied in final years in, bringing unprecedented beneficial results. Thanks to conducting fifteen conferences of the family group in the district of Bytów over twenty children missed to institutions social and behavioral, and it stayed in related and unrelated foster families and around their families.
Keywords: family; children; conference of the family group; welfare; social exclusion